Lot Eight / Lote Ocho - Small, Rachel (UnderCurrents: Journal of Critical Environmental Studies, 2017)
<!-- P { margin-bottom: 0.21cm; } --> This piece was submitted as a spoken-word poem. A recording can be found on UnderCurrents' SoundCloud: https://soundcloud.com/undercurrentsatyork/lot-eight-lote-ocho Special thanks to Ruben Esguerra, audio engineer on the recording. [Author's Note - Content warning: this poem discusses sexual, gendered, and other forms of violence.] Dedicated to the women of Lot 8 who are fighting like hell for justice not only on their land in Guatemala, but who have brought their historic fight into Canadian courts as well... Find full piece in .pdf below.